Racial isolation and exposure to airborne particulate matter and ozone in understudied US populations: Environmental justice applications of downscaled numerical model output. (July 2016) - Bravo, Mercedes A.; Anthopolos, Rebecca; Bell, Michelle L.; Miranda, Marie Lynn
Abstract: Background: Researchers and policymakers are increasingly focused on combined exposures to social and environmental stressors, especially given how often these stressors tend to co-locate. Such exposures are equally relevant in urban and rural areas and may accrue disproportionately to particular communities or specific subpopulations. Objectives: To estimate relationships between racial isolation (RI), a measure of the extent to which minority racial/ethnic group members are exposed to only one another, and long-term particulate matter with an aerodynamic diameter of < 2.5 μ (PM2.5 ) and ozone (O3 ) levels in urban and nonurban areas of the eastern two-thirds of the US. Methods: Long-term (5 year average) census tract-level PM2.5 and O3 concentrations were calculated using output from a downscaler model (2002–2006). The downscaler uses a linear regression with additive and multiplicative bias coefficients to relate ambient monitoring data with gridded output from the Community Multi-scale Air Quality (CMAQ) model. A local, spatial measure of RI was calculated at the tract level, and tracts were classified by urbanicity, RI, and geographic region. We examined differences in estimated pollutant exposures by RI, urbanicity, and demographic subgroup (e.g., race/ethnicity, education, socioeconomic status, age), and used linear models to estimate associations between RI and air pollution levels in urban, suburban, and rural tracts. Results: High RI tracts (≥ 80th percentile) had higher average PM2.5 levels in each category of urbanicity compared to low RI tracts (< 20th percentile), with the exception of the rural West. Patterns in O3 levels by urbanicity and RI differed by region. Linear models indicated that PM2.5 concentrations were significantly and positively associated with RI. The largest association between PM2.5 and RI was observed in the rural Midwest, where a one quintile increase in RI was associated with a 0.90 μg/m 3 (95% confidence interval: 0.83, 0.99 μg/m 3 ) increase in PM2.5 concentration. Associations between O3 and RI in the Northeast, Midwest and West were positive and highest in suburban and rural tracts, even after controlling for potential confounders such as percentage in poverty. Conclusion: RI is associated with higher 5 year estimated PM2.5 concentrations in urban, suburban, and rural census tracts, adding to evidence that segregation is broadly associated with disparate air pollution exposures. Disproportionate burdens to adverse exposures such as air pollution may be a pathway to racial/ethnic disparities in health. Highlights: Investigates urbanicity, racial isolation, and air pollution across eastern US. First study to examine racial isolation and air pollution in nonurban areas. More racially isolated census tracts have higher long-term PM2.5 independent of urbanicity. Association between segregation and PM2.5 is strongest in Midwest rural communities.